rozwiąż (5x+y)(x-2y)-x(4x+y) =oraz 6x-3x(2-x)(5x+1)=​

Odpowiedź :

Odpowiedź:

1)x^2-10xy-2y^2-4x^2

2) -27x^2+15x^3

Szczegółowe wyjaśnienie:

1) (5x+y)(x-2y)-x(4x+y)=

=5x^2-10xy-2y^-4x^2

=x^2-10xy-2y^2-4x^2

2)6x-3x(2-x)(5x+1)=

=6x+(-6x+3x^2)*(5x+1)

=6x-30x^2-6x+15x^3+3x^2

= -30X^2+15x^3+3x^2

= -27x^2+15x^3

Odpowiedź:

(5x+4)(x-2y)-x(4x+y)=

5x^2-10xy+4x-8y-4x^2-xy

x^2-11xy+4x-8y

6x-3x(2-x)(5x+1)=6x+(-6x+3x^2)×(5x+1)=

6x-30x^2-6x+15x^3+3x^2=

-27x^2+15x^3

Szczegółowe wyjaśnienie:

jak cos to np 4x^2 to jest 4x do potegi 2